Tropical fruits - Tate, D. J. M. (Singapore : Archipelago Press, 2007)
Introduces readers worldwide to some of the best tropical fruit, with hints on how to recognize them, enjoy them, get the best out of them
First published in paperback, 2007
Originally published: Singapore: Archipelago, 2003
Includes bibliographical references (p. 95) and index
Keywords: Tropical fruit